Lenin's electoral strategy from 1907 to the October Revolution of 1917 : the ballot, the streets or Both - Nimtz, August H.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
This book is the first full-length study of Lenin's party building project and writings on elections, looking in detail at his leadership of the Bolshevik wing of the Russian Social Democratic Labor Party in the four state Dumas from 1906 to the beginning of the First World War.
Keywords: Science; Science, general